Occupation diversification strategy of Delas Village of Southern Bangka in a post-tin mining era - Herdiyanti Herdiyanti (Masyarakat, Kebudayaan dan Politik, 2019)
This research refers to the social-economic situation of Bangka people, in particular, a community in Delas Village in the Air Gegas district of Southern Bangka. The aim of this research is to explain the survival strategies adopted by Delas people in the post-tin mining era. This research applies descriptive qualitative research. Findings in the field show that a factor that influences survivability in the post-mining era is the creativity of the Delas people. To provide a livelihood in the post-mining era, individuals are encouraged to be more active and creative to more wisely manage natural resources. People also possess various assets in natural and physical capital, financial capital, human, and social capital. Based on research, creative process conducted by make diversification of occupation from natural resource. Occupational diversification is a new post-mining era survival strategy of the Delas people. This research shows that various activities are performed as part of this strategy, such as utilizing former mining land for freshwater fish farming or rearing livestock, which in turn minimizes mining activities.